Improving Students’ English Pronunciation by Using Hypermedia in E-Learning Activity - Madya Giri Aditama; Prasetyawan Aji Sugiharto (LP. Ma'arif Janggan Magetan, 2021)
Abstract: Hypermedia systems are computer-based multimedia systems that provide interactive and link-based navigation that allow the information in digital form. The researcher strives to know the effects of hypermedia in teaching English pronunciation whether or not it can enhance the pronunciation skills of 21st-century learners in e-learning activities. It is a descriptive qualitative study. The data were an average score of pre-test and post-test, also interview results of 20 students of international classes of Universitas Muhammadiyah Surakarta which chosen randomly. Data in the form of pre-test and post-test scores as well as the results of interviews with students about hypermedia. The results of the study show that the average score of the pre-test was 71,37, and the average score of the post-test was 77,62. The level of achievement of the students in the post-test was good. This study also concluded that hypermedia in teaching English pronunciation was one of the media to reinforce students’ motivation in enhancing English knowledge and skills, especially in pronunciation. Abstrak: Sistem hypermedia merupakan sistem multimedia berbasis komputer yang menyediakan navigasi yang interaktif dimana menyajikan informasi dalam bentuk digital. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh hypermedia sebagai metode pembelajaran dalam meningkatkan kemampuan pelafalan bahasa Inggris (pronunciation) siswa dalam aktivitas e-learning. Penelitian ini berupa penelitian deskriptif kualitatif. Sumber data atau responden dalam penelitian ini adalah 20 mahasiswa kelas internasional Universitas Muhammadiyah Surakarta yang dipilih secara acak sebagai sampel. Data berupa hasil nilai pre-test dan post-test serta hasil wawancara kepada siswa mengenai hypermedia. Hasil dari penelitian ini diperoleh nilai rata-rata dalam pre-test adalah 71,37; nilai rata-rata dalam post-test 77,62. Level pencapaian siswa dalam post-test adalah baik. Dan dapat disimpulkan bahwa hypermedia dapat memotivasi siswa untuk belajar pelafalan bahasa Inggris dengan baik. Dari hasil penelitian ini juga dapat disimpulkan bahwa hypermedia merupakan media yang dapat mendorong dan meningkatkan motivasi di dalam pengajaran pelafalan Bahasa Inggris. DOI: https://doi.org/10.33399/edukasia.v2i1.41